Thirty Meter Running Skill Test of Rugby Athletes - Joko Mubarok; Muhammad Imam Rahmatullah; Japhet Ndayisenga (CV. FOUNDAE, 2022)
Running speed is one of the main factors for the achievement of rugby athletes. The test of the sprint running skills of the University of Muhammadiyah Surakarta (UMS) Rugby athletes is the analysis of this study, where the athletes tested are athletes who play as defenders. In this research, the type of research used is quantitative research with ex post facto methods. Collecting research data using valid tests. Then analyzed with categorization and SPPS to determine the average running speed of rugby athletes. The results showed that two athletes were in poor condition, two were in the moderate category, three were in high condition, and three were in excellent condition. Meanwhile, the average running speed of all athletes is in the moderate category. Based on these results, it is necessary to improve the speed quality of rugby athletes, especially defenders, so they can help defend quickly.